Effect of Peer Support Group on the Level of Depression in Type 2 Diabetic Patients: A Randomized Clinical Trial - Zahra Rahimi; Mohsen Kooshan; Rahim Akrami; Mostafa Rad (Mashhad University of Medical Sciences, 2019)
Background: Depression is one of the most common psychological problems in diabetic patients. Peer support groups focusing on shared experiences may affect patients' minds. Aim: This study aimed to evaluate the effect of peer support groups on the level of depression in type 2 diabetic patients. Method: This randomized controlled clinical trial was conducted on 64 patients with type 2 diabetes in Sabzevar, Iran, during 2018. The level of depression was assessed before and six weeks after the intervention using the Beck Depression Inventory-II. The intervention group attended peer support group sessions, whereas the control group received training by a nurse at the diabetes center. The data were analyzed in STATA software (version 12) using repeated measures ANOVA. Results: According to the results, the mean ages of the patients were 51.7±9.2 and 51.5±8.5 years in the intervention and control groups, respectively. Moreover, the total depression scores in the intervention and control groups were obtained at 24.7±2.9 and 23.3±2.8, respectively. However, these values changed to 15.1±6.1 and 24.3±4.8 immediately after the intervention, as well as 15.8±6.1 and 24.7±4.3 six weeks later, in the intervention and control groups, respectively. The repeated measures ANOVA revealed a significant difference between these two groups in terms of the effect of the group (P<0.001), the effect of time (P<0.001), and mutual effect (P<0.001). Implications for Practice: Peer support group could decrease the level of depression in diabetic patients therefore, it is recommended that peer education be considered as a part of patients' therapeutic program with the aim of reducing mental symptoms.